The Efforts of the City Corner Literacy Community to Increasing Children's Interest in Reading - Sofyan, Hanifah Sari; Lestari, Gunarti Dwi; Yusuf, Ali; Yulianingsih, Wiwin (Universitas Negeri Semarang, 2024)
The low interest in reading among children in Semampir sub-district is caused by the lack of parental awareness of the importance of reading, as well as children's habits that prioritize playing gadgets over reading. This study aims to describe the efforts of the City Corner Literacy, community in literacy activities, efforts made to improve literacy, supporting and inhibiting factors, and implications of literacy programs for children. This study uses a qualitative approach with a qualitative descriptive research type, and data collection techniques through observation, interviews, and documentation. The results of the study indicate the existence of facilities in the form of books and a comfortable place for literacy activities for children. Efforts made by the community to improve literacy are holding activities that are not related to books, as well as adding to the book collection. Supporting factors come from the family environment and the outside environment. The implications of literacy programs for children in Semampir sub-district have a positive impact, such as children's enthusiasm in participating in literacy activities, gaining new experiences, and changes in children's habits from just playing to also reading.